A cross encryption scheme for data security storage in cloud computing environment. Issue 1 (21st March 2023) - Kang, Haiyan; Deng, Jie
Cloud computing is one of the popular technologies in the development of information technology. Cloud computing not only provides users with high-performance computing, but also meets the needs of large-scale data storage. However, because the storage service provided by cloud computing is completely transparent to users, users cannot understand whether their data is safe in the cloud computing environment. The resulting distrust has brought great obstacles to the development of cloud computing. Therefore, this paper first describes the basic knowledge and system architecture of cloud storage, and analyses the development status of cloud storage. Secondly, in order to ensure the storage security of user data in the cloud computing environment, this paper studies the data encryption algorithm, and proposes a cross encryption scheme of data security storage in the cloud computing environment. Finally, the scheme is compared with the traditional hybrid encryption method. The experimental results show that the scheme has the advantages of good encryption and decryption effect, fast execution speed and high security. It is an ideal scheme for data security storage in cloud computing environment.